Detection and prevalence of multidrug-resistant Klebsiella pneumoniae strains isolated from poultry farms in Blitar, Indonesia - DIAN AYU PERMATASARI; ADIANA MUTAMSARI WITANINGRUM; FRESHINTA JELLIA WIBISONO; Mustofa Helmi Effendi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Permatasari DA, Witaningrum AM, Wibisono FJ, Effendi MH. 2020. Detection and prevalence of multidrug-resistant Klebsiella pneumoniae strain isolated from poultry farms in Blitar, Indonesia. Biodiversitas 21: 4642-4647. Antibiotics are commonly used as therapy and disease control in humans and animals. However, the widespread use of antibiotics may also trigger the rise of antibiotic resistance. Therefore, the aim of this study was to study the occurrence of Multidrug-Resistant (MDR) of Klebsiella pneumoniae from poultry farms in Blitar. Chicken cloacal swabs were collected from 63 poultry farms (32 broilers and 31 layers) were taken randomly, using total samples 160 broilers and 155 layers. The collected swab samples were inoculated on MacConkey agar medium for isolation and identification. Single colonies were isolated after primary positive cultures and identified by using the IMViC test and TSIA. 28 (8.88%) out of samples were positive for Klebsiella pneumoniae. The antimicrobial confirmation test showed that 53.57% of the K. pneumoniae isolates were Multi-Drug Resistance (MDR) bacteria. The percentage of MDR bacteria against different antibiotics included ampicillin 75%, Erythromycin 42.86%, Tetracycline 35.72%, Sulfamethoxazole 32.14% and Streptomycin 21.4%. This study confirms that the percentage of resistant isolates of Klebsiella pneumoniae from 5 antimicrobial agents of broiler chicken is higher than layer chicken. The presence of multidrug-resistant bacteria is a threat to public health and livestock. The impact of these conditions leaves a limited treatment option as chicken farmers in Indonesia still using antibiotics without veterinarian supervision.